2018
DOI: 10.1002/rra.3264
|View full text |Cite
|
Sign up to set email alerts
|

Catchment characteristics predicting nitrogen and phosphorus losses in Finland

Abstract: Empirical relationships between catchment properties and nutrient losses are often derived from spatially restricted data, which hampers the ability to more widely generalize the results. In this study, we regressed the catchment characteristics and the losses of total nitrogen (TN) and total phosphorus (TP) for all monitored catchments in Finland with adequate data (n = 59, from the year 2000 to 2011). TN loss was found to increase with the percentage of arable land and amount of point source loading and to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…However, excess P losses from agricultural areas to receiving water bodies can cause water quality impairments. It has been shown that field and lake percentages as well as soil type strongly control total phosphorus (TP) loss from catchments in Finland (Röman et al 2018;Vuorenmaa et al 2002). Thus, TP transported in rivers is often monitored to evaluate excess P losses and the effectiveness of mitigation measures intended to constrain P losses from agricultural sites (e.g., Tattari et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, excess P losses from agricultural areas to receiving water bodies can cause water quality impairments. It has been shown that field and lake percentages as well as soil type strongly control total phosphorus (TP) loss from catchments in Finland (Röman et al 2018;Vuorenmaa et al 2002). Thus, TP transported in rivers is often monitored to evaluate excess P losses and the effectiveness of mitigation measures intended to constrain P losses from agricultural sites (e.g., Tattari et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0 License. (Turunen et al, 2017;Bechmann, 2012;Ulén et al, 2012;Turtola et al, 2007;Øygarden et al, 1997) leading to high spatial variability in erosion and further in the transport of suspended sediment loads from different sites and catchments (Röman et al, 2018;Ulén et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have estimated the average erosion from fields to vary from 55 to 2100 kg ha-1 yr-1 (Lilja et al, 2017a;Puustinen et al, 2010) and earlier modelling approaches have estimated the average erosion of all agricultural lands to be 418-485 kg ha-1 yr-1 (Lilja et al, 2017b;Puustinen et al, 2010). These Fig.s are relatively low in global and European scales (Borrelli et al, 2017;Panagos et al, 2015c), however, in respect to the ecological state of water bodies in northern latitudes, they result in significant negative impacts in surface waters and in the Baltic Sea (Ulén et al, 2012), particularly through transport of phosphorus along with the eroded soil particles (Röman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The key process causing soil erosion is hydrological, and soil particles are detached from the surface by the kinetic energy of rain drops and surface runoff causing slaking, swelling and dispersion (Bissonnais, 2016;Ulén et al, 2012;Jarvis et al, (Turunen et al, 2017;Bechmann, 2012;Ulén et al, 2012;Turtola et al, 2007;Øygarden et al, 1997) leading to high spatial variability in erosion and further in the transport of suspended sediment loads from different sites and catchments (Röman et al, 2018;Ulén et al, 2012).…”
Section: Introductionmentioning
confidence: 99%